An integrated process for the production of lignocellulosic biomass pyrolysis oils using calcined limestone as a heat carrier with catalytic properties. (1st October 2016) - Veses, A.; Aznar, M.; Callén, M.S.; Murillo, R.; García, T.
Graphical abstract: Highlights: An integrated process for upgraded bio-oil production was assessed. Catalytic pyrolysis of wood biomass was studied in an Auger reactor. Char combustion was studied in a fluidised-bed reactor. Full regeneration of heat carrier catalytic properties was not accomplished. Char combustion was feasible from environmental and operational points of view. Abstract: The production of upgraded bio-oils by an integrated process using a mixture of calcined limestone and sand as a heat carrier with catalytic properties was experimentally studied at pilot scale. The integrated process consisted of two main steps: biomass catalytic pyrolysis in an Auger reactor for bio-oil production and char combustion in a fluidised-bed combustor for heat carrier heating and regeneration. A temperature of 450 °C was fixed as an optimum value to carry out the catalytic pyrolysis step. Temperatures ranging from 700 to 800 °C were assessed in the char combustor. Process simulation demonstrated that solid recirculation from the combustor to the pyrolysis reactor was marginally affected in this temperature range. However, an optimum char combustion temperature of 800 °C was selected from an environmental point of view, since lower polyaromatic emissions were detected whilst NOx emissions were kept under the legislation limits. Under designated conditions, several pyrolysis-combustion cycles were carried out. A moderate deactivation of the catalyst by partial carbonation was found. This fact makes necessary the incorporation of a purge and an inlet of fresh heat carrier in order to maintain the bio-oil quality in the integrated process.